Characteristics of Chief Technology Officers and Radical Innovation - Chung, Doohee; Kang, Minhyung (International Journal of Innovation and Technology Management, 2019)
This study examines how characteristics of chief technology officer (CTO) drive radical innovation of the firm. Using data of 140 firms in US manufacturing industries, this study finds that the characteristics of the CTO explains a significant proportion of a firm's relative radicalness even after controlling for CEO and top management team (TMT) characteristics, organizational capabilities, and other firm characteristics. Specifically, a CTO's diverse functional experience increases a firm's radicalness. In terms of individual prior functions, marketing experience was significantly related to radical innovation. In addition, the CTO's diverse industrial experience increases the firm's radicalness. In contrast to the existing theories, the CTO's education level, tenure and age showed insignificant effects. However, the number of degrees in engineering and science showed significant effect on the performance of radical innovation. These results of the analysis on firm-level radicalness provide implications for both academics and practitioners.
Keywords: chief technology officer; executive decision; Radical innovation